Efforts to Optimize the Managerial Competence of Madrasah Heads in Improving Teacher Performance in MIN 3 Jakarta for the 2019/2020 School Year - Ecep Hasanudin (Journal of Social Research, 2023)
The era of the head of the madrasah in moving the life of the madrasah to achieve thegoal can be done with two things, namely; The head of the madrasah acts as a central force that becomes the driving force of the life of the madrasah and, the head of the madrasah must understand their duties and functions (educators) for the success of the madrasah, and have concern for staff and students. In this research, the problem is formulated as follows: (a) Can the managerial competence of the Head of Madrasah improve teacher performance? (b). What are the steps to create Teacher Performance with the implementation of managerial Head of Madrasah? While the objectives of this study are: (a) To find out whether teacher performance can improve by applying the managerial competence of the Head of Madrasah (b). want to know how the steps to create Teacher Performance with the implementation of managerial Head of Madrasah. In terms of Optimizing Managerial Competence, the Head of Madrasah has been able to Improve Teacher Performance, this is marked by a significant increase in each cycle, cycle I by 63% and cycle II by 100%. This shows the success of optimizing the managerial competence of the head of the madrasah in improving the performance of teacher.